Demography of a subarctic population of Clethrionomys gapperi : numbers and survival - Fuller, W. A. (Canadian Journal of Zoology, 1977)
Intensive (capture–mark–release) studies on a 2.25-ha grid, and extensive (catch per unit effort) studies on a 30-km segment of the Mackenzie Highway at latitude 61° N, revealed a dubious peak in 1970, and an unequivocal peak in 1974, in both May and August numbers of Clethrionomys gapperi. The minor peak was associated with good survival in the prepeak winter overwintered adults, but not young of the year, displayed good summer survival. Almost 70% of animals known to be alive at the end of August survived the winter before the major peak, and all ages survived well during the peak summer. Less than 5% of marked animals survived the postpeak winter. The prepeak winter was characterized by low and fluctuating temperatures beneath the snow, whereas the postpeak winter had high and uniform subnivean temperatures. Thus, the hypothesis that winter mortality, and hence abundance, is governed by the severity of conditions in the subnivean microenvironment was falsified, but the result is consistent with the hypothesis that animals in the increase phase were qualitatively different from those in the decline phase.